Nano-sized drug delivery systems to potentiate the immune checkpoint blockade therapy - Shim, Man Kyu; Song, Su Kyung; Jeon, Seong Ik; Hwang, Kwang Yeon; Kim, Kwangmeyung (Ashley Publications Ltd., 2022)
Introduction Immune checkpoint blockade (ICB) therapy is now FDA-approved for the treatment of various tumor types. By removing inhibitory signals for T-cell activation and disrupting the immune escape mechanism of tumor cells, ICB therapy has shown considerable efficacy with complete tumor regression in patients. However, patients respond poorly to this therapy and show limited response rates owing to the immunosuppressive tumor microenvironment (ITM) in cold tumors. Areas covered In this review, recent advances and progress in the use of nano-sized drug delivery system (Nano-DDS) to potentiate the ICB therapy by reversing cold tumors with an ITM into immunogenic hot tumors are discussed. The types of immunogenic cell death (ICD) inducers that initiate or enhance antitumor immune responses are classified, and their extensive combination with immune modulators using Nano-DDS is highlighted. Expert opinion Nano-DDS can be efficiently combined with ICD inducers and immune modulators and trigger a potent antitumor immune response based on a comprehensive approach to the cancer-immunity cycle.